2014
DOI: 10.1097/coh.0000000000000064
|View full text |Cite
|
Sign up to set email alerts
|

Liver fibrosis in HIV

Abstract: Therefore, aging of the liver in HIV may play a much more pivotal role in the future considering age-related effects, coinfection with hepatotropic viruses and the toxicity of long-term antiviral treatment. Thus, adequate monitoring of liver disease and development of management algorithms are clearly needed to optimize outcome and care of the aging liver in an HIV-infected individual.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 30 publications
2
35
0
Order By: Relevance
“…In these publications a wide range of prevalence for abnormal LS values were identified (Han et al, 2013; Lui et al, 2016; Merchante et al, 2010; Rockstroh et al, 2014). Using these applied cutoff values we had a similarly wide prevalence range (9.9–44.55%).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In these publications a wide range of prevalence for abnormal LS values were identified (Han et al, 2013; Lui et al, 2016; Merchante et al, 2010; Rockstroh et al, 2014). Using these applied cutoff values we had a similarly wide prevalence range (9.9–44.55%).…”
Section: Discussionmentioning
confidence: 99%
“…Age is a well-known risk factor for LF in non-alcoholic fatty liver disease (NAFLD) and HCV-infected patients (Chan, Patel & Choi, 2016). However, data about age-related fibrosis in the HIV mono-infected population are scarce (Rockstroh et al, 2014). To date, only a few descriptive studies identified significant association with age and LF in this patient population (Blanco et al, 2011; Han et al, 2013; Merchante et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations